THE DIAGNOSIS MODEL BUILDING ON THE BASIS OF NEGATIVE SELECTION PARADIGM USING THE PRINCIPLE OF DETECTOR ASKING - Zaitsev, S. A.; Subbotin, S. A. (Radio Electronics, Computer Science, Control, 2012)
A new negative selection model using masked detectors with training method has been developed. Various stopping criteria for the training method have been investigated. The stopping criterion is proposed. It allows to terminate training procedure, to speedup training process and to reduce computational resources.